GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 3,1982 - NISHIO, Fumihiko; OHMAE, Hirokazu; ISHIKAWA, Masao (National Institute of Polar Research, 1986)
P(論文) departmental bulletin paper